1990
DOI: 10.1007/bf01313419
|View full text |Cite
|
Sign up to set email alerts
|

Light intensity and the feeding behaviour of herring,Clupea harengus

Abstract: An infra-red sensitive video-recording technique was used to study the effects of darkness and light intensities from 0.0001 to 270 photopic lx on the feeding behaviour of herring (Clupea harengus L.). When offered natural zooplankton, consisting of a mixture of Calanus finmarchicus, Euchaeta norvegica, Oithona similis, Balanus sp. nauplii, and crustacean nauplii as prey, the fish fed by biting (snapping) at light intensities above a threshold of 0.001 lx and were size-selective, taking the larger organisms fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 17 publications
(8 reference statements)
3
70
0
Order By: Relevance
“…Experiments with the herring, Clupea harengus, suggest that the threshold for visual feeding in clupeids lies somewhere between 0.01 and 0.001 lux, or 10 25 to 10 26 alelux, depending on the type of prey source used and direction of the light source (Blaxter 1964;Batty et al 1990). The feeding rate experiments, behavioral observations, and field gut-content analysis in our study all suggest that light significantly increases feeding rates on mysids down to 10 27 alelux relative to darker conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments with the herring, Clupea harengus, suggest that the threshold for visual feeding in clupeids lies somewhere between 0.01 and 0.001 lux, or 10 25 to 10 26 alelux, depending on the type of prey source used and direction of the light source (Blaxter 1964;Batty et al 1990). The feeding rate experiments, behavioral observations, and field gut-content analysis in our study all suggest that light significantly increases feeding rates on mysids down to 10 27 alelux relative to darker conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with other clupeids suggest that the light intensity necessary for visual feeding is $ 10 times greater than the light level likely to be experienced by alewives feeding within the mysid layer. For example, Batty et al (1990) found that the Atlantic herring, Clupea harengus, ceased particulate feeding at a light level of 0.001 lux when fed a natural assemblage of zooplankton; however, when fed Artemia nauplii, the visual threshold was even higher (, 0.01 lux)-a value that is over two orders of magnitude brighter than the 10 24 lux that limits mysid ascent (Gal et al 2004;Boscarino et al 2009a,b). Previous studies that have attempted to model mysid predator distribution as a function of light and prey abundance have used encounter rate functions, which assume that alewives are not capable of using light levels available at night to enhance their feeding rates on mysids, regardless of moon phase (Mason and Patrick 1993;Jensen et al 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While schooling is considered primarily as an antipredator or feeding adaptation (Pitcher & Parrish 1993), it appears to be affected by a number of environmental factors in addition to the presence of predators and prey. The effect of light level on schooling behaviour and its sensory basis is widely documented (Glass et al 1986;Batty et al 1990). However, the effects of other environmental factors, such as oxygen saturation, temperature, turbidity and windspeed, on schooling behaviour have rarely been investigated (see Weetman et al (1998Weetman et al ( , 1999 for the effect of temperature on schooling behaviour).…”
Section: (C) Hypoxia and Trade-offs In Schooling Behaviourmentioning
confidence: 99%
“…: Blaxter 1973, Matthews 1984, Swenson and Matson 1976, Wales 1984 and fl!St feeding (e.g. : Batty 1987, Batty et al 1990, Ellertsen et al 1980) is extensively investigated.…”
Section: Introductionmentioning
confidence: 99%